2022
DOI: 10.3390/jof8030318
|View full text |Cite
|
Sign up to set email alerts
|

Virulence Factors of Sporothrix schenckii

Abstract: Sporothrix schenckii is one of the etiological agents of sporotrichosis. In this review, we discuss the virulence factors that have been proven to participate in the S. schenckii-host interaction. Among these known factors, we can find cell wall glycoproteins, adhesins, melanin, extracellular vesicles, and dimorphism. Furthermore, the morphological transition of S. schenckii in response to environmental conditions such as pH and temperature represents a means by which the fungus is able to establish mycosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 90 publications
0
14
0
Order By: Relevance
“…Judging from the pieces of information above, it is evident that taxonomic developments have promoted important advances in epidemiological scenarios, parasite–host interactions, sensitivity to antifungal agents, and the biology of these pathogens. Therefore, it is imperative to recognize Sporothrix species in the clinical scenario [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. The diagnosis of sporotrichosis down to genus or species level can bring benefits to treatment and thus impact the clinical outcome of patients, and in the case of the felines, avoid the dispersion of the fungus into the feline and human populations [ 32 , 64 ].…”
Section: A Primer On Sporothrix and Sporotrichosismentioning
confidence: 99%
“…Judging from the pieces of information above, it is evident that taxonomic developments have promoted important advances in epidemiological scenarios, parasite–host interactions, sensitivity to antifungal agents, and the biology of these pathogens. Therefore, it is imperative to recognize Sporothrix species in the clinical scenario [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ]. The diagnosis of sporotrichosis down to genus or species level can bring benefits to treatment and thus impact the clinical outcome of patients, and in the case of the felines, avoid the dispersion of the fungus into the feline and human populations [ 32 , 64 ].…”
Section: A Primer On Sporothrix and Sporotrichosismentioning
confidence: 99%
“…Thermo-dimorphism, glycans, adhesins, secreted vesicles and melanin have all been associated with the ability of the fungus to cause disease in the mammalian host (Garcia-Carnero and Martinez-Alvarez, 2022;Garcia Carnero et al, 2018). However, their contributions to virulence remain to be confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, at least one case of sporotrichosis, transmitted by an imported infected cat, has been reported in the United Kingdom (Rachman et al, 2022). Thermo-dimorphism, glycans, adhesins, secreted vesicles and melanin have all been associated with the ability of the fungus to cause disease in the mammalian host (Garcia-Carnero and Martinez-Alvarez, 2022; Garcia Carnero et al ., 2018). However, their contributions to virulence remain to be confirmed experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Another important function of the fungal cell wall is to serve as a molecular scaffold to display molecules that can contribute in pathogenesis and virulence [ 29 , 30 ]. Here, García-Carnero and Martínez-Álvarez provide an up-to-date review paper on the most recent information related with virulence factors already rerpoted in S. schenckii [ 31 ]. These include cell wall adhesins, melanin production, extracellular and intracellular proteinases, extracellular vesicles, and biofilm formation [ 31 ].…”
mentioning
confidence: 99%
“…Here, García-Carnero and Martínez-Álvarez provide an up-to-date review paper on the most recent information related with virulence factors already rerpoted in S. schenckii [ 31 ]. These include cell wall adhesins, melanin production, extracellular and intracellular proteinases, extracellular vesicles, and biofilm formation [ 31 ]. As part of the adhesins repertoire found on the S. schenckii cell wall, García-Carnero et al showed that the cell wall peptidorhamnomannan is composed of a heterogeneous mix of different proteins, and among them Hsp60 and Pap1 are the most abundant ones [ 32 ].…”
mentioning
confidence: 99%